Validation of the English Basal and Squamous Cell Carcinoma Quality of Life (BaSQoL) Questionnaire. Issue 3 (March 2020) - Yu, Wesley Y.; Waalboer-Spuij, Rick; Bremer, Rebecca; Lu, Brian; Aroyan, Christine; Crow, Lauren; Grekin, Roy; Neuhaus, Isaac; Yu, Siegrid; Arron, Sarah T.; Hollestein, Loes M.
Abstract : BACKGROUND: Keratinocyte carcinomas (KC) impact patient quality of life (QoL). There is a need for validated QoL instruments specific to KC. The Basal and Squamous Cell Carcinoma QoL (BaSQoL) questionnaire was developed to comprehensively measure issues of importance to patients with KC. OBJECTIVE: To validate and characterize the BaSQoL questionnaire for QoL measurement after diagnosis and treatment of KC. METHODS: This was a prospective, observational study. Patients with basal cell carcinoma (BCC) or squamous cell carcinoma (SCC) were asked to fill out BaSQoL, Skin Cancer Index (SCI), and Hospital Anxiety and Depression Scale (HADS) questionnaires. Descriptive statistics and classical test theory were used to assess validity. RESULTS: One hundred eighty-seven subjects enrolled in this study: 122 with BCC and 65 with SCC. One hundred seventy-one subjects (91.4%) completed questionnaires at all 3 time points; 16 patients (8.6%) were lost to follow-up. Overall performance using classical test theory was good, with good internal consistency (Cronbach's α 0.63–0.80). BaSQoL subscales were strongly correlated with subscales of the SCI, demonstrating convergent validity, and weakly correlated with HADS, showing divergent validity. CONCLUSION: The English language version of BaSQoL has good face, content, and construct validity. This study validates BaSQoL for use in English-speaking patients with BCC and SCC. Abstract : Supplemental Digital Content is Available in the Text.